Probing the low surface brightness outskirts of Milky Way dSphs: Sextans. Issue Volume 11:Issue S321(2015) (21st March 2017) - Cicuéndez, Luis; Battaglia, Giuseppina; Irwin, Mike; McMonigal, Brendan; Lewis, Geraint; Bate, Nick
Abstract: Faint dwarf galaxies such as those found around the Milky Way (MW) display the largest known dynamical mass-to-light ratios (up to several 100s M⊙ /L⊙ ). However, tidal interaction with the MW may impact the dynamical equilibrium in the outer parts of some of these objects, and partly affect the derived dynamical M/L. Assessing this is crucial for the study of the dark matter content of these galaxies. A clear sign of ongoing tidal disturbance would be the presence of tidal tails. These are expected to be low surface brightness features, hence difficult to detect from star counts in systems where contamination is also present, e.g. from foreground MW stars. At present we have searched for these sorts of tidal features in the Sextans dwarf spheroidal galaxy (dSph), by adopting the Matched Filter Method (e.g. Rockosi et al. 2002), a very efficient technique to decontaminate stellar density maps with a high ratio of contamination versus source density (dwarf galaxies outer regions or ultra faint dwarf galaxies). We also calculate structural parameters from the position of stars without requiring spatial binning (Richardson et al. 2011), through a Bayesian MCMC (Foreman-Mackey et al. 2013).